Puso ay ingatan hypertension ay labanan - Alfabeto, Ace Robert; Anglopez, Mae Therese (University of the Philippines Visayas, College of Arts and Sciences, Division of Biological Sciences, 2009)
Hypertension is a condition wherein there is significant increase of blood pressure (bp) in the individual. Although hypertension is not a disease, it is often associated with other diseases especially chronic vascular disease (CVD) and stroke, both of which are serious.